STRUCTURAL FEATURES OF THE CHLOROPLAST GENOME OF THE RARE TULIP SPECIES TULIPA ALBERTI, INCLUDED IN THE RED BOOK OF KAZAKHSTAN - Tussipkan, D.; Shevtsov, V.; Ramazanova, M.; Orken, A.; Rakhimzhanova, A.; Shevtsov, A.; Manabayeva, Sh. (Eurasian Journal of Applied Biotechnology, 2026)
Tulipa alberti is an important plant species used for ornamental purposes in Asia, Europe, and North Africa. This study reports the complete chloroplast genome features of this endangered species collected from Kazakhstan using Illumina sequencing technology. The results revealed that the T. alberti chloroplast genome is highly conserved. The genome size is 152,006 bp, comprising a pair of inverted repeats (IR) of 26,330 bp, a large single-copy (LSC) region of 82,169 bp, and a small single-copy (SSC) region of 17,172 bp. The overall GC content is 36.58%. A total of 131 genes were identified, including 85 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Twenty-eight genes contained introns with lengths ranging from 540 to 2,620 bp. The nucleotide diversity (π) was 0.003257. Analysis of simple sequence repeats (SSR) identified 159 SSR loci in the T. alberti genome, mainly distributed in the LSC region (63.19%), SSC region (18.39%), and IR region (14.37%). Six types of SSR motifs (mono-, di-, tri-, tetra-, penta-, and hexanucleotides) were detected. The most polymorphic protein-coding (CDS) genes were rpoC2, cemA, rbcL, rpl36, psbH, rps3, rpl22, ndhF, ycf1, and matK, which exhibited high sequence variability (SV = 2.581–6.102) and nucleotide diversity (π = 0.004–0.010). Relative synonymous codon usage (RSCU) analysis revealed both preferred and less frequently used codons. The characterization of the T. alberti chloroplast genome provides valuable insights into the conservation of genetic resources, evolutionary and phylogenetic relationships of this rare species. However, to date, data on the complete sequencing and comprehensive bioinformatics analysis of the chloroplast genome of T. alberti remain limited. This study contributes to biodiversity preservation in Kazakhstan and offers a basis for developing effective conservation strategies at the molecular level.